2012
DOI: 10.1093/erae/jbs032
|View full text |Cite
|
Sign up to set email alerts
|

Inertia in disinvestment decisions: experimental evidence

Abstract: In this paper we analyse the timing of disinvestment decisions by applying a real options approach to explain the experimentally observed disinvestment behaviour of agricultural entrepreneurs. Within this framework the tendency to postpone exit and termination choices can be rationalised. The validity of the real options theory is assessed by means of economic experiments. Our results show that real options models can predict actual disinvestment decisions better than traditional investment theory. Nevertheles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
25
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 52 publications
6
25
0
1
Order By: Relevance
“…Nevertheless, the observed disinvestment reluctance is even more pronounced than predicted by the ROA. These findings are consistent with previous investigations (Oprea et al 2009;Sandri et al 2010;Musshoff et al 2013;Maart-Noelck and Musshoff 2013).…”
Section: Test Of H1 'Roa Superiority To Npv'supporting
confidence: 94%
See 2 more Smart Citations
“…Nevertheless, the observed disinvestment reluctance is even more pronounced than predicted by the ROA. These findings are consistent with previous investigations (Oprea et al 2009;Sandri et al 2010;Musshoff et al 2013;Maart-Noelck and Musshoff 2013).…”
Section: Test Of H1 'Roa Superiority To Npv'supporting
confidence: 94%
“…Decision-makers tended to wait even longer than indicated by the ROA. In a recent study, Musshoff et al (2013) experimentally analysed the exit decision of 63 farmers using the ROA. Their results showed that the ROA predicted the actual disinvestment decisions better than the classical investment theory.…”
Section: Theory and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…The study revealed a relationship between the disinvestment decisions given by participants and the disinvestment triggers calculated according to a formal optimal stopping benchmark compatible with real-options reasoning. The findings of this study are consistent with those reported by Musshoff et al (2012), who carried out a disinvestment experiment with farmers. All these aforementioned studies mainly focus on the investment behavior of students and entrepreneurs in Western industrialized countries.…”
Section: Introductionsupporting
confidence: 92%
“…Oprea et al (2013) investigated learning effects of students during an investment experiment. Sandri et al (2010) and Musshoff et al (2013) also analysed the predictive power of the RO approach in an experimental setting. However, both studies focused on a disinvestment treatment, which was modelled as a dynamic problem of optimal stopping.…”
Section: Introductionmentioning
confidence: 99%